Peranan Kiai Kemas H.M.Zen Mukti (1338-1400 H/ 1919-1980 M) Dalam Politik Dan Dakwah Di Palembang - Okta Supriani (Program Studi Sejarah Peradaban Islam UIN Raden Fatah Palembang, 2021)
This paper discusses the role of Ki.Kms.H.M. Zen Mukti in politics and religion in Palembang. Ki.Kms.H.M. Zen Mukti is a former Masjumi member, his contribution to politics and da'wah in Palembang is quite capable. The accusation of Masyumi's involvement in the PRRI (Revolutionary Government of the Republic of Indonesia) provides a dark note for former Masjumi members during the New Order era. In this study tries to reveal the other side of the former Masjumi party members and analyze why the former Masjumi members transitioned to cultural Islam during the New Order era. This study uses three data collection techniques such as literature study, interviews and documentation. The type of research used is qualitative by referring to historical research procedures, the sociology approach is used as an auxiliary science in research by focusing on social stratification theory and role theory to analyze the position and status of Ki.Kms.H.M. Zen Mukti. This research describes the progress of Ki.Kms.H.M. Zen Mukti in political and religious activities in Palembang. This research also reveals that in the New Order era, the role of bureaucratic clerics became suspended in political matters. The triumph of the Masjumi party members during the Old Order became dim in the hands of the New Order regime. The New Order regime's intervention against political clerics also influenced their role in the life of the state. The purpose of this study was to determine the life background and role of Ki.Kms.H.M. Zen Mukti as a bureaucratic scholar who contributes to politics and religion in Palembang.